Sensitivity analysis for III–V/Si tandem solar cells: A theoretical study. (20th July 2017) - Thway, Maung; Ren, Zekun; Liu, Zhe; Chua, Soo Jin; Aberle, Armin G.; Buonassisi, Tonio; Peters, Ian Marius; Lin, Fen
Abstract: Material and structural parameters may affect the efficiency of a tandem solar cell differently from the way they do in a single-junction solar cell. We fabricated a III–V/Si four-terminal tandem solar cell and developed an opto-electronic model simulating this device. The optical properties were simulated with the transfer matrix method, while the electrical properties were simulated using the numerical device simulator PC1D. For this simulated tandem structure, we determined the parameters which have the largest potential impact on the device efficiency. A sensitivity analysis of the impact of these parameters on the device efficiency was also performed. In addition, to reduce the cost of the tandem solar cells, we identified the parameters that do not require tight control during the manufacturing process. The Si cell was simulated both as a single-junction cell and as the bottom cell of a tandem device. Finally, we determined those device parameters that are more critical in a tandem configuration than in a single-junction configuration.